MENINGKATKAN POSISI TAWAR KELUARGA SEBAGAI KONSUMEN DALAM MENGHADAPI KRISIS EKONOMI - Sri Wening Sri Wening (LPMPP Universitas Negeri Yogyakarta, 1998)
?he plunln ctting economy experienced by Indonesiansin the last few months have raised difficulties for almost allfa niliesa s consumers, though the lcvei of difficulty may vary. In[he ongoing economic crisis, every family's buying power ofcourse decreases bccause the income of the family rem; insunchanged while the price of basic necessities conllnues toskyrocket. There are actually families having enough funds butthey cannot get the goods needed because they are not found inthe market. In such a condition, the power control of everyfanlily over each fanlily menlber is h ghlyn eeded to determinethe attitude in the lamily. ?he fa nily as consumers mustinevitably conduct self- introspection to sce whethcr they havcbecn consumers with a highly critical and inclcpcndcotbargaining positioil.'lherelore, certain efforts must be made in the fact t)Ithe econonlic crisis in order to maintain the quality the famjly'sstandards of living for the interest of the family. One of thcefforts that can be made lor the purpose of improving thebargaining position of the family is by improving the quality of'communication in the family, cultivating the consumingawarenes of the family, and also maintaining the presence of'behavioral examples partaining to the bargaining position fro111the mother or the father.